Creating Space for Emancipatory Human Security: Liberal Obstructions and the Potential of Agonism1. Issue 2 (16th November 2012) - PETERSON, JENNY H.
Abstract : Peterson, Jenny H. (2012) Creating Space for Emancipatory Human Security: Liberal Obstructions and the Potential of Agonism. International Studies Quarterly, doi: 10.1111/isqu.12009 © 2012 International Studies Association The human security agenda, as currently operationalized by the majority of powerful states and institutions, exhibits a distinct liberal character, simultaneously contributing to and legitimizing the dominant liberal peacebuilding approach. As such, there has been a crowding out of alternative conceptions of human security, including those which focus on emancipation. This latter approach to human security offers a more transformative vision through its focus on issues such as hegemony, power, and freedom. Paths to such forms of human security have yet to materialize, largely due to the characteristics of a liberal–internationalist approach which has narrowed the political space in which challenges to the status quo can be imagined and realized. In its failure to allow for a genuine plurality of voices and in its insistence on creating false consensus, liberal peacebuilding blocks the emancipatory promise of a genuine shift from state to human security. A potential starting point for imagining alternatives to liberal peacebuilding and thus the creation of emancipatory forms of human security is to consider the role and possibilities for agonistic modes of politics and peacebuilding. Transforming inevitable differences that are part of human society into agonistic relationships—where differences exist and are negotiated among adversaries (as opposed to enemies)—opens up the political space required to challenge dominant liberal approaches to human security and enables a shift toward the emancipatory model.